Effect of Halal-Certified Slaughterhouses and Storage Time on Microbiology and Organoleptic Quality of Broiler Chicken Meat - Irfan, Irfan; Lubis, Yanti Meldasari; Ryan, Muhammad; Yunita, Dewi; Lahmer, Rabya A (UIN Sunan Gunung Djati Bandung, 2023)
Chicken slaughterhouses play an essential role in producing halal chicken. In previous study, only nine halal-certified chicken slaughterhouses in Banda Aceh. This study determined the effect of halal-certified slaughterhouses and storage time on broiler chicken meat's microbiology and organoleptic quality. This study uses a factorial randomized block design with two factors (halal-certified slaughterhouses (the slaughterhouse which already has a halal certificate (S1) and the slaughterhouse which has not yet halal certified (S2) and storage time (0 hours (P1), 3 hours (P2), 6 hours (P3), and 9 hours (P4)). Each treatment repeats three times. Data were statistically analyzed using analysis of variance (ANOVA) and continued with Duncan's New Multiple Range Test (DNMRT) at a 5% level. Samples were analyzed for total plate counts (TPC), pH, and descriptive organoleptic tests of meat color, aroma, moisture, elasticity, and skin color. The results showed that the quality of meat from chickens slaughtered at halal-certified slaughterhouses was better than that of not halal-certified slaughterhouses in terms of lower microbial number and pH value, as well as the higher value of descriptive organoleptic characteristics (meat color, aroma, elasticity, and skin color). There is no difference found in meat moisture.